Application of Android-Based E-Module in Occupational Health, Safety, and Environmental Protection and Industrial Work Culture Material - Nurrokhman , Tedi; Khumaedi, Muhammad; Sutopo, Yeri (Journal of Vocational and Career Education, 2025)
The problem with learning Occupational Health, Safety, and Environmental Protection (OHS-EP) and Industrial Work Culture is that most students show a lack of enthusiasm in participating in lessons and struggle to understand the teaching material, particularly in important aspects such as the application of OHS-EP procedures, the use of personal protective equipment (PPE), and understanding the principles of industrial work culture. This study aims to apply and analyze the feasibility and effectiveness of an Android-based E-Module to improve the cognitive abilities of vocational school students on the subjects of OHS-EP and Industrial Work Culture. The research follows the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). A pre-experimental method with a two-group pretest-posttest design was employed, comparing an experimental class and a control class consisting of 70 students. The results indicate that the assessment of the material, media, and test instruments for the E-Module is deemed suitable for use. Statistical analysis reveals a significant improvement in the experimental class compared to the control class after the intervention. The results of the N-Gain test show that the experimental class experienced a 53.4% improvement (moderate category), while the control class showed only a 21.5% improvement, indicating enhanced cognitive abilities among the students. This study emphasizes the positive impact of technology on education and reinforces the importance of innovative teaching methods to improve cognitive abilities in students.